Conceptualising the Role of International Capital Flows for Housing Markets - Michael Richter; Johannes-Gabriel Werner (Intereconomics, 2016)
The existing literature on the role of international capital flows for housing markets can be classified into approaches which focus on the macro relationship between the current account and housing prices on the one hand and studies which specify more specific transmission channels on the other. Building on this literature, we conceptualise the role of international capital flows for housing markets via four central transmission channels. We suggest that by differentiating among these channels, the risk build-up potential of capital flows for housing markets can be evaluated more precisely than in the early literature on global imbalances.
Keywords: 330; Kapitalmobilität; Wohnungsmarkt; Immobilienfinanzierung